Gender, Trust, and Tax Compliance: The Mediating Effect of Fairness Perception - Yesaya Biely Febrian; Imas Nurani Islami, S.Pd, M.Sc. (President University Press, 2020)
For governments around the world, voluntary tax compliance is critical as they try to minimize budget deficits. In order to boost tax compliance, traditional methods can be expensive to be applied. This study aims to analyze the impact of social factors on the tax compliance intentions of individuals. Supported results were found in a survey of 150 Indonesian taxpayers regarding the effect of social factors on tax compliance. We sum up that gender and trust in government have a significant influence on perception of fairness and perception of fairness on compliance decision. In addition, perception of fairness also succeeded in bridging or mediating gender and trust in government towards compliance decisions. This study might help tax authorities in developing more efficient approaches with less cost to improve taxpayer compliance.